Repurposing Treatment of Wernicke–Korsakoff Syndrome for Th-17 Cell Immune Storm Syndrome and Neurological Symptoms in COVID-19: Thiamine Efficacy and Safety, In-Vitro Evidence and Pharmacokinetic Profile - Vatsalya, Vatsalya; Li, Fengyuan; Frimodig, Jane; Gala, Khushboo S.; Srivastava, Shweta; Kong, Maiying; Ramchandani, Vijay A.; Feng, Wenke; Zhang, Xiang; McClain, Craig J. (Frontiers in Pharmacology, 2021)
Coronavirus disease identified in 2019 (COVID-19) can be complicated by the Th17 cell-mediated IL-17 proinflammatory response. We tested if thiamine can effectively lower the Th17 response in a clinical study (Proinflammatory state in alcohol use disorder patients termed as disease controls [DC]) and corroborated the results using an in vitro study. We developed an effective dose range and model for key pharmacokinetic measures with the potential of targeting the cytokine storm and neurological symptoms of COVID-19. Three-week 200 mg dose of thiamine was administered to sixteen DC patients. Eight healthy volunteers (HV) were also included in this investigation. A subsequent in vitro study was performed to validate the effectiveness of thiamine (100 mg/day equivalent [0.01 µg/ml]) treatment in lowering the Th17 proinflammatory response in a mouse macrophage cell line (RAW264.7) treated with ethanol. Based on recent publications, we compared the results of the IL-17 response from our clinical and in vitro study to those found in other proinflammatory disease conditions (metabolic conditions, septic shock, viral infections and COVID-19) and effective and safe dose ranges of thiamine. We developed a pharmacokinetic profile for thiamine dose range as a novel intervention strategy in COVID-19. DC group showed significantly elevated proinflammatory cytokines compared to HV. Thiamine-treated DC patients showed significant lowering in IL-17 and increase in the IL-22 levels. In humans, a range of 79-474 mg daily of thiamine was estimated to be effective and safe as an intervention for the COVID-19 cytokine storm. A literature review showed that several neurological symptoms of COVID-19 (~45.5% of the severe cases) occur in other viral infections and neuroinflammatory states that may also respond to thiamine treatment. Thiamine, a very safe drug even at very high doses, could be repurposed for treating the Th17 mediated IL-17 immune storm, and the subsequent neurological symptoms observed in COVID-19. Further studies using thiamine as an intervention/prevention strategy in COVID-19 patients could identify its precise anti-inflammatory role.